2009
DOI: 10.19030/ajbe.v2i3.4046
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Financial (Accounting) Literacy: A Comparison Of Audit Committee Members And Business Students

Abstract: <p>While financial literacy is important for an audit committee in discharging its duties there is no authoritative guidance or definition and limited empirical research as to what constitutes financial literacy of audit committees and business students. Coates et al. conducted a study that examined the financial literacy of corporate board members and MBA students at the University of Chicago using an instrument developed by Schipper and Weil. Their findings suggest that both groups lack the appropriate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…To fulfill such important responsibilities, having financial knowledge greatly helps the audit committee (Musallam 2020). Acquisition of financial expertise is not only possible through experience, and having education and experience together can create a financial expert (Giacomino et al 2009). After the scandal and the collapse of big companies such as Enron and WorldCom, Section 407 of the Sarbanes-Oxley Act in 2002 required companies to set up an audit committee consisting of independent members and at least one financial expert (Salehi et al 2018b).…”
Section: H8mentioning
confidence: 99%
“…To fulfill such important responsibilities, having financial knowledge greatly helps the audit committee (Musallam 2020). Acquisition of financial expertise is not only possible through experience, and having education and experience together can create a financial expert (Giacomino et al 2009). After the scandal and the collapse of big companies such as Enron and WorldCom, Section 407 of the Sarbanes-Oxley Act in 2002 required companies to set up an audit committee consisting of independent members and at least one financial expert (Salehi et al 2018b).…”
Section: H8mentioning
confidence: 99%
“…However, level of education, work location, and father's education were not significantly correlated with financial literacy and investment decisions. Giacomino, Wall, and Akers (2009) examined the financial literacy among undergraduate accounting and finance students at a private Midwestern university. The writers used an instrument developed and used previously by Coates et al (2007) as an extension to study the financial literacy of corporate board members and MBA students at the University of Chicago.…”
Section: Financial Literacy and Investment Decisionsmentioning
confidence: 99%
“…In some countries, several laws and regulations have been set to provide important requirements for financial knowledge and expertise even for members of audit committees. For example, in 1999 the New York Stock Exchange (NYSE) added a rule requiring each company to have an audit committee comprising of independent directors who are financially literate and including at least one financial expert (Giacomino, Wall, and Akers, 2009). This article seeks to explore the relationship between financial and accounting literacy and individual investors' participation in the UAE financial markets.…”
Section: Introductionmentioning
confidence: 99%
“…However, the studies on accounting literacy are quite limited Feast at al., (1999) the new approach to teaching provides learning support for all students by clarifying, developing and practicing the required tertiary literacy skills. The findings of Giacomino et al (2009) indicate the undergraduate students also lack financial literacy. Elson et al (2011) found that the students' average scores on the pre-test were less than the anticipated average scores.…”
Section: Introductionmentioning
confidence: 98%